Dobre praktyki edukacji wielokulturowej na przykładzie Społecznego Gimnazjum nr 20 „Raszyńska” w Warszawie - Figiel, Angelika (Kultura-Społeczeństwo-Edukacja, 2018)
This article is an attempt to present the good practices of intercultural education. By the introducing into the main problems, the author presents the education rules of foreigners in the Polish education system, indicating the most important aspects of Polish law regulations. Then defines the one of the most important concepts of intercultural education and multicultural education, discussing its main goals and tasks. The crucial question raised in the text is the role of the school in the intercultural education and shaping of intercultural competence in education among pupils by the teacher. At this point, the author attempts to answer the question whether and how Polish schools and teachers are prepared to accept foreign children? And what is the role of the teacher in intercultural education? In the second part of the text, they presented good practices of intercultural education as an example the Social Secondary School No. 20 “Raszyńska” in Warsaw.